2021
DOI: 10.1038/s41438-021-00528-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteomic and metabolomic analyses reveal the importance of aroma precursor accumulation and storage in methyl jasmonate-primed tea leaves

Abstract: In response to preharvest priming with exogenous methyl jasmonate (MeJA), tea plants adjust their physiological behavior at the molecular level. The whole-organism reconfiguration of aroma formation from the precursor to storage is poorly understood. In this study, we performed iTRAQ proteomic analysis and identified 337, 246, and 413 differentially expressed proteins in tea leaves primed with MeJA for 12 h, 24 h, and 48 h, respectively. Furthermore, a total of 266 nonvolatile and 100 volatile differential met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Studies have also shown that MeJA can affect the biosynthesis of fruit components, such as carotene, chlorophyll, and vitamins (Saniewski and Czapski, 1983;Pérez et al, 1993;Wolucka et al, 2005). In addition, Shi et al (2021) showed that MeJA induced the accumulation of tea (Camellia sinensis L.) aroma precursors and improved the quality of fresh leaves. Moreover, it has been observed that the application of MeJA significantly enhanced the flavor quality of fruits and vegetables, such as peaches (Prunus persica L. Batsch), strawberries (Fragaria × ananassa Duch.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that MeJA can affect the biosynthesis of fruit components, such as carotene, chlorophyll, and vitamins (Saniewski and Czapski, 1983;Pérez et al, 1993;Wolucka et al, 2005). In addition, Shi et al (2021) showed that MeJA induced the accumulation of tea (Camellia sinensis L.) aroma precursors and improved the quality of fresh leaves. Moreover, it has been observed that the application of MeJA significantly enhanced the flavor quality of fruits and vegetables, such as peaches (Prunus persica L. Batsch), strawberries (Fragaria × ananassa Duch.…”
Section: Introductionmentioning
confidence: 99%
“…Omics technology provides a powerful tool for tea plant research, which is characterized by its high throughput, high sensitivity, and systematic nature [ 23 ]. Metabolomics can be used for qualitative and quantitative analysis of low-molecular-weight substances produced in tea plants in a specific period [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The volatile compounds released by fresh tea leaves are responsible for tea aroma [ 59 ]. Previous studies revealed that the aroma quality of black and oolong teas can be improved by spraying the leaves of tea plants with MeJA, which results in increased emission of desirable aroma compounds, including terpenes and aromatic compounds [ 58 , 60 ]. Thus, the changes to volatile emissions induced by the JA–SA synergism may be exploited to improve tea processing.…”
Section: Discussionmentioning
confidence: 99%